2020
DOI: 10.2147/dddt.s229302
|View full text |Cite
|
Sign up to set email alerts
|

<p>The Traditional Chinese Medicine Compound, GRS, Alleviates Blood–Brain Barrier Dysfunction</p>

Abstract: Introduction: Traditional Chinese medicine (TCM) provides unique advantages for treatment of ischemic stroke, an aging-related vascular disease. Shengmai powder (GRS) is composed of three active components, specifically, ginsenoside Rb1, ruscogenin and schisandrin A, at a ratio of 6:0.75:6. The main objective of this study was to evaluate the effects of GRS on blood-brain barrier (BBB) dysfunction under conditions of middle cerebral artery occlusion/reperfusion (MCAO/R). Methods: C57BL/6J mice subjected to MCA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 54 publications
2
9
0
Order By: Relevance
“…In this study, IL-35 treatment inhibited caspase-1-mediated EC injury in vivo and in vitro. Consistent with these results, previous studies have shown that many Chinese herbal medicines with anti-inflammatory effects (such as hispidulin and ruscogenin) can ameliorate BBB injury after ischemic stroke by markedly suppressing the expression of IL-1β and cleaved caspase-1 (36,37).…”
Section: Discussionsupporting
confidence: 84%
“…In this study, IL-35 treatment inhibited caspase-1-mediated EC injury in vivo and in vitro. Consistent with these results, previous studies have shown that many Chinese herbal medicines with anti-inflammatory effects (such as hispidulin and ruscogenin) can ameliorate BBB injury after ischemic stroke by markedly suppressing the expression of IL-1β and cleaved caspase-1 (36,37).…”
Section: Discussionsupporting
confidence: 84%
“…Ophiopogon japonicus has been demonstrated as a pharmacological Chinese medicinal herb in distinct diseases, including diabetes, cancers and inflammatory diseases (Chen et al, 2016). Since ruscogenin, the primary effective steroid sapogenin from Ophiopogon japonicus, has been reported to ameliorate ischemic-induced inflammatory pathway (Guan et al, 2013) or blood-brain barrier dysfunction (Zhang et al, 2020), its role in POCD was investigated in the present study.…”
Section: Discussionmentioning
confidence: 96%
“…Monocrotaline-induced pulmonary hypertension (Bi et al, 2013), cerulein-induced acute pancreatitis (Ercan et al, 2019) and particulate matter-induced acute lung injury (Wang et al, 2021b) were ameliorated by ruscogenin through its anti-inflammatory capacity. Cerebral ischemic-induced inflammatory pathway was also suppressed by ruscogenin (Guan et al, 2013), and ruscogenin alleviated ischemia/reperfusion-induced blood-brain barrier dysfunction (Zhang et al, 2020). Since surgery is indicated to promote the secretion of pro-inflammatory factors and blood-brain barrier dysfunction to induce neuroinflammation during the development of POCD (Hovens et al, 2016), the role of ruscogenin in anesthetic-induced POCD was investigated in this study.…”
Section: Enzyme-linked-immunosorbent Serologic Assay (Elisa)mentioning
confidence: 97%
“…Applying the results of in vitro experiments to clinical treatment is still challenging. The advantages of new formulations of traditional Chinese medicine in the treatment of glioma have gradually emerged, and the research level of targeted Chinese medicine in glioma is also increasing [19,20]. Secondly, the mechanism of the effect of lentinan on proliferation and apoptosis of human astrocytoma U251 cells is still unclear.…”
Section: Discussionmentioning
confidence: 99%